Penerapan Real Time Passenger Information System untuk Peningkatan Kualitas Pelayanan pada Bus Transmetro Pekanbaru - Susianti, Elva (Politeknik Caltex Riau, 2023)
Over time, the number of vehicles in big cities will increase, as will the city of Pekanbaru. The rate of increase in the volume of vehicles that is greater than that of road development will result in congestion. To overcome this problem, the Pekanbaru Regional Government implemented the Pekanbaru Trans Metro Bus system, known as TMP in 2009. The disproportionate number of buses operating and the length of operating lines caused the time intervals between buses in one place to be very long. The uncertainty of when the bus will arrive at the bus stop is one of the factors causing this system failure. The position and speed of the bus obtained from the GPS module will be read by NodeMCU Lolin V3 (Controller) and sent to the MySQL database on the PCR server. The data will be used to determine the time to the next stop. The time data will be posted on the website. In addition, the equipment will be equipped with an RFID reader and an e-Bus card for making an e-money-based bus ticket payment system.